Study habits in high school students belonging to the diploma program international baccalaureate - Cardich San Juan, Roxana (2018)
The primary objective of the research was to determine the extent to which the International Baccalaureate Diploma Program changes the study habits in the academic performance of students in the last years of secondary school. Study habits such as study techniques, organizational skills, exam-preparation techniques, and techniques used in class, as well as students’ level of distractibility, were analyzed and compared. The study used a longitudinal design with three time points and a control group. The study started with a sample of 73 students; however, due to experimental mortality, the work was performed with 50 students, of which 29 made up the control group and 21 the experimental group. For the experimental group, when overall scores are examined in relation to study habits, the results show changes over time. Specifically, for the experimental group, changes were observed in students’ study techniques, organization, preparation for exams and distractibility. The differences found in study habits between the two groups should be considered cautiously, given that they were present before the program started, due to which they are not attributable to the Diploma Program. The assertions invite reflection on the value of developing cognitive and emotional skills, as well as the possibility of implementing this type of programs starting in the first years of basic education.